Assessing Sensory Processing Problems in Children With and Without Attention Deficit Hyperactivity Disorder. (1st February 2015) - Pfeiffer, Beth; Daly, Brian P.; Nicholls, Elizabeth G.; Gullo, Dominic F.
ABSTRACT Aims: This exploratory study investigated whether children with attention-deficit/hyperactivity disorder (ADHD) are at greater risk than children without ADHD for problems with sensory processing and if certain sensory systems are more closely associated with the core symptoms of ADHD, specifically inattention and hyperactivity/impulsivity. Methods: The sample included 20 children with ADHD and 27 children without ADHD, ages 5 to 10 years. Assessments included the Sensory Processing Measure-Home Form and the Conners 3rd edition-Parent Short Form. Results: After controlling for age, children with ADHD exhibited more sensory processing problems on all scales of the Sensory Processing Measure with small to medium effect sizes observed (η2 = .27 to .61). For children with ADHD, the Social Participation (r = .50) and Planning and Ideas (r = .73) subtests of the Sensory Processing Measure were significantly associated with hyperactivity/impulsivity, but not with inattention on the subtests of the Conners Parent Short Form. Conclusion: The results suggest the importance of assessing sensory processing issues in children with ADHD to guide in the intervention process.